Implementasi Restrukturisasi Kredit Sebagai Strategi Penurunan Kredit Bermasalah Pada Koperasi Serba Usaha Semeton Bali Satya - Ni Komang Devi Kristianti; Cokorda Gde Bayu Putra; Rai Dwi Andayani W (UNHI Press, 2025)
The purpose of this study was to determine the factors that caused problem loans in Semeton Bali Satya Multi-Purpose Cooperative and to determine the strategy to reduce problem loans in Semeton Bali Satya Multi-Purpose Cooperative. The author conducted the research located at Semeton Bali Satya Multi-Purpose Cooperative located at Jl. Trenggana No. 156 Br. Anggabaya, Penatih Village, East Denpasar District, Denpasar City, Bali 80238, Indonesia. In this study, the subject was the Chairman of KSU Semeton Bali Satya. Meanwhile, the object of this research is the Implementation of Credit Restructuring as a Strategy to Reduce Problematic Credit Located in the Semeton Bali Satya Multipurpose Cooperative. The main data for this study were obtained directly from the field from questions asked to the managers and administrators of the Semeton Bali Satya Multipurpose Cooperative. Secondary data for this study were obtained from journal theses on the implementation of credit restructuring as a strategy to reduce problematic credit. Based on the type of research which is field research, the data collection techniques used in this study are interview, observation and documentation techniques. The data analysis process begins by reviewing all available data from various sources, namely from interviews, observations that have been obtained, both field notes, official documents, pictures, photos, and so on. The results of the study show that the main factors causing problematic credit at KSU Semeton Bali Satya are the post-pandemic economic impact and high inflation. Members' incomes that have not fully recovered and the increase in the price of basic necessities have created significant financial pressure. KSU Semeton Bali Satya has implemented several important strategies. Steps such as credit restructuring, use of the 5 C approach in credit analysis, recording member characteristics, and tightening credit requirements are part of the cooperative's efforts to reduce the risk of problematic credit. In addition, the cooperative also increases credit supervision with more intensive monitoring and provides education and assistance to members regarding personal financial management.